Analisis Kandungan Formalin, Pestisida, dan Jamur pada Beberapa Jenis Ikan Asin - I Made Hadi Purnomo; Shanti Dwita Lestari; Ace Baehaki (Universitas Sriwijaya, 2017)
Purpose of this research was to know formaldehyde content, pesticides (organochlorine and organofosfat), and molds on various type of dried salted fish. This research used survey methods, sampling and laboratory analysis. The fish used are salted siamese gourami fish (Trichogaster pectoralis), salted bagrid catfish (Hemibagrus nemurus), salted longjaw thryssa fish (Thryssa setirostris), salted snakehead fish (Channa striata) and salted fish anchovies (Stolephorus sp.). Result showed that salted snakehead fish (Channa striata) and salted anchovy fish (Stolephorus sp.) in August and September are positive to formaldehyde content. All tested samples were negative to pesticide residues. The result of molds test revealed that all samples still met National Food and Drug Agency (BPOM) RI 2009 standards which were less than 1x105 colonies/gram.